2010
DOI: 10.3109/17477160903545163
|View full text |Cite
|
Sign up to set email alerts
|

Increased oxidative stress and altered substrate metabolism in obese children

Abstract: Pediatric obesity, a major risk factor for cardiovascular diseases and diabetes, has steadily increased in the last decades. Although excessive inflammation and oxidation are possible biochemical links between obesity and cardiovascular events in adults, little information is available in children. Furthermore, effects of gender and fitness on the interaction between dyslipidemia and oxidative or inflammatory stress in children are mostly unknown. Therefore, we measured systemic markers of oxidation (F2-isopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 40 publications
4
31
0
Order By: Relevance
“…Oxidative stress has been associated with obesity, hyperglycemia, hypertension and atherosclerosis [23,24,25,26]. Previous studies demonstrated that the earliest signs of CHD, such as coronary artery fatty streaks, are already present in childhood and rapidly increase during adolescence, particularly in those with elevated BMI [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress has been associated with obesity, hyperglycemia, hypertension and atherosclerosis [23,24,25,26]. Previous studies demonstrated that the earliest signs of CHD, such as coronary artery fatty streaks, are already present in childhood and rapidly increase during adolescence, particularly in those with elevated BMI [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…This reaction leads to the formation of MDA, as is indicated by the elevated levels of TBARS in overweight or obese children [16,50]. However, the result of the biomarker of lipid peroxidation (TBARS) in this study was distinct from the evidence presented in the literature for school-aged children [16,22], and the reason for this difference is not completely understood. The lower SOD and CAT activities was similar to those of other studies, which demonstrated the presence of a low antioxidant defense in overweight and obese children [16].…”
Section: Discussionmentioning
confidence: 61%
“…Higher levels of leptin, resistin, soluble TNF receptors 1 (sTNFR1) and 2 (sTNFR2), monocyte chemoattractant protein-1 (MCP-1), regulated upon activation normal T-cell expressed and secreted (RANTES), interleukin-8 (IL-8), interferon-inducible protein 10 (IP-10), monokine induced by interferon-γ (MIG), ROS and cortisol, as well as lower levels of adiponectin, BDNF and antioxidant enzymes in school-age overweight or obese children can be observed [8,10,19,20,21,22,23,24,25]. Another study already demonstrated elevated C-reactive protein (CRP) levels, another inflammatory marker, in preschool obese children [26].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, obese children displayed widespread alterations in their lipid profile, plasma glucose, and insulin compared to the control group. 11 Habib et al conducted a case-control study and compared obese children and adolescents aged 5-17 years with healthy control participants matched for age and gender. They also showed significant elevations in proinflammatory adipocytokines (tumour necrosis factor-a and IL-6) and an oxidative stress biomarker (MDA), as well as significant decreases in antioxidant defense mechanisms (glutathione, zinc levels, and superoxide dismutase activity) among obese individuals compared to the control group.…”
Section: Discussionmentioning
confidence: 99%